Enhanced degradation of extracellular polymeric substances by yeast in activated sludge to achieve sludge reduction. (June 2023) - Wan, Pengfei; Liu, Ying; Zhang, Quandi; Jiang, Li; Chen, Heping; Lv, Wenzhou
Graphical abstract: Highlights: Yeast degraded PN, PS, amino acids, and fluorescent components in EPS. Yeast transformed macromolecular organics to small molecular ones in EPS. Addition of 0.75 g/L of yeast enhanced the dewaterability of AS. Yeast reduced hydrophilic organics or functional groups in EPS. Yeast enhanced the AS dewaterability and reduced the in-situ biomass in SBR. Abstract: Candida Tropicalis was used to improve the dewaterability of activated sludge (AS) and reduce its biomass by degrading EPS in AS. The protein, polysaccharide, and hydrophilic amino acids in EPS decreased by 54.50, 29.20, and 61.01%, respectively. Meanwhile, molecular weight distribution indicated that yeast degraded macromolecular organics into small molecular ones. The direct addition of yeast to AS was more conducive to EPS degradation. With the addition of 0.75 g/L of wet yeast cells and 24 h of aeration enhanced the dewaterability of AS. The CST and MLSS decreased by 24.44 and 10.51%, respectively. After 30 days of operation of lab-scale continuous SBRs, the CST and MLSS of AS were reduced by 6.37 ± 2.01 and 3.57 ± 0.52%, respectively. FTIR spectroscopy results showed that some hydrophilic functional groups were reduced. This study provides a new approach for the in-situ reduction of AS in wastewater treatment plant.